The prevalence and clinical implications of pancreatic fat accumulation identified during a medical check-up. Issue 41 (15th October 2021) - Okada, Kosuke; Watahiki, Takahisa; Horie, Kaoru; Takayama, Takako; Aida, Yuka; To, Keii; Shida, Takashi; Ishige, Kazunori; Nishiyama, Hiroyuki; Shoda, Junichi; Suzuki, Hideo
Abstract : Abstract: Fatty pancreas (FP) is characterized by pancreatic fat accumulation and the subsequent development of pancreatic and metabolic complications. However, FP has not been categorized in the manual for abdominal ultrasound in cancer screening and health check-ups in Japan, and the pathology of FP has not been fully elucidated. Nine hundred and nineteen people who underwent a medical check-up had the severity of their pancreatic fat accumulation categorized after transabdominal ultrasonographic examination. The relationships between FP, lifestyle-related diseases, and fatty liver disease at this time were assessed using stratification analysis. The prevalence of FP was 46.8% (430/919). People with FP were more likely to be male and had higher prevalences of lifestyle-related diseases, including fatty liver disease. Men and women were similarly represented in each tertile of pancreas brightness. Older age; high waist circumference, triglyceride and glucose index, serum low-density lipoprotein-cholesterol, hepatic steatosis index; and low serum amylase were associated with the presence of severe FP. Moreover, the group with severe liver steatosis had a higher prevalence of FP and a higher pancreatic brightness score. Logistic regression analysis showed that individuals with liver steatosis were more likely to have severe FP. The severity of FP is associated with features of lifestyle-related diseases and the severity of liver steatosis. These findings suggest that high visceral fat content is associated with more severe fatty pancreas as a phenotype of ectopic fat accumulation, as well as fatty liver disease. Abstract : Supplemental Digital Content is available in the text